Factors Affecting the Quality of Life of Chronic Kidney Disease Patients Based on the Simple Quality of Life Scale - Alfanira (CV. Get Press Indonesia, 2024)
Chronic kidney disease (CKD) greatly affects the quality of life of patients undergoing hemodialysis, who often face physical limitations, emotional distress, and social challenges. This study aimed to identify factors influencing their quality of life using the Simple Quality of Life Scale (SQOLS). A cross-sectional design was conducted involving 50 hemodialysis patients at RSUP Dr. M. Djamil Padang. Data were collected through SQOLS questionnaires covering physical, emotional, social, environmental, and occupational domains, and analyzed using descriptive statistics and multiple linear regression.Results showed that most patients experienced reduced quality of life, with an average SQOLS score of 60.4. Significant factors affecting quality of life were anxiety levels (β = –0.45, p < 0.01), occupational status (β = 0.32, p < 0.05), and social support (β = 0.28, p < 0.05). High anxiety lowered quality of life, while strong social support and active employment improved it. These findings emphasize the importance of psychosocial interventions, including counseling and support groups, to reduce anxiety and strengthen social networks. In conclusion, psychological and social factors play a key role in shaping the quality of life of CKD patients and should be addressed in patient care.